Peran Perencanaan Dalam Pembangunan Lembaga Pendidikan Islam Modern - Luthfie Noor Fithriasari; Muhammad Yahya Ashari (Islamic Education Management Study Program of STIT al Urwatul Wutsqo Jombang, East Java, Indonesia, 2023)
In building a modern Islamic educational institution, planning is required which is the key to effectiveness in carrying out educational activities and improving the quality of education in order to achieve goals. Modern Islamic education planning uses systems from modern educational institutions, but does not abandon the values ??of Islamic teachings. Education is the spearhead of success, so modern Islamic education requires planning to obtain results in accordance with the objectives. Because in planning there are expectations and also methods that will be used to achieve educational goals. The purpose of this article is to determine the role of planning in the development of modern Islamic education and matters related to planning in modern Islamic education. This research is qualitative research with a library study approach through literature in the form of journals, books and scientific articles as the main object. Planning is a series or policies implemented by considering the strengths of opportunities, challenges and obstacles. The role of modern Islamic education development planning, as a tool to guarantee the quality of modern Islamic education development, as a tool for achieving educational goals effectively and efficiently, as a means to ensure the smooth achievement of development goals, as a means to clarify the vision, mission and development strategy of modern Islamic education, as a logical and systematic tool to change the system for the better.